Separated and cooperative influence of components of ice cloud on total extinction of optical radiation - Shefer, Olga V. (Journal of Quantitative Spectroscopy and Radiative Transfer)
For set of crystals with and without taking into account nonsphericity and preferential orientation, there are presented the calculation results that generalize the features of the spectral behavior of the extinction efficiency factor of radiant energy. The influence of various physico-chemical characteristics of scatterers on extinction is demonstrated. The scheme is proposed for comparative analysis of the extinction coefficient of visible and infrared radiation for different components of ice cloud. Considering a medium containing methane and large ice plates, there is demonstrated the scheme to estimate cooperative and separated contributions of dispersed and gas components to the total extinction by the mixture.